2011
DOI: 10.1007/s13313-011-0102-6
|View full text |Cite
|
Sign up to set email alerts
|

The field resistance of potato cultivars to foliar late blight and its relationship with foliage maturity type and skin type in Brazil

Abstract: The use of resistant cultivars is the preferred control method for plant diseases. This approach is attractive owing to its high efficacy, low cost, and ease of implementation. This work aimed to assess the resistance of potato cultivars to foliar late blight (Phytophthora infestans) under different environmental conditions. It further aimed to assess the relationships between resistance to foliar late blight and foliage maturity type and between resistance to foliar late blight and the skin type of the potato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…These clones were obtained by selection of the population generated from crosses between potato genitors used in the Embrapa breeding program and clones of the B3 population selected by the CIP for late blight horizontal resistance (LANDEO et al, 2001), as previously confirmed (MULEMA et al, 2004;WULFF et al, 2007), and which, are known to present high yields of tubers (NAMUGGA et al, 2018). The reaction of the cultivars Ágata, Asterix, Bintje, and Ana, confirmed their susceptibility, as reported by other authors (GOMES et al, 2009;DUARTE et al, 2012). In the specific case of cultivar Eliza, the instability of the reaction to the more aggressive isolate demonstrates the apparent presence of major R genes in this clone.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These clones were obtained by selection of the population generated from crosses between potato genitors used in the Embrapa breeding program and clones of the B3 population selected by the CIP for late blight horizontal resistance (LANDEO et al, 2001), as previously confirmed (MULEMA et al, 2004;WULFF et al, 2007), and which, are known to present high yields of tubers (NAMUGGA et al, 2018). The reaction of the cultivars Ágata, Asterix, Bintje, and Ana, confirmed their susceptibility, as reported by other authors (GOMES et al, 2009;DUARTE et al, 2012). In the specific case of cultivar Eliza, the instability of the reaction to the more aggressive isolate demonstrates the apparent presence of major R genes in this clone.…”
Section: Resultssupporting
confidence: 87%
“…Although the use of resistant potato cultivars is one of the most desirable management strategies for late blight control in potatoes, the majority of cultivars available for the Brazilian growers are susceptible or moderately susceptible to the pathogen (GOMES et al, 2009;DUARTE et al, 2012) or show pathotype-specific resistance, which is inefficient over time (FRY, 2008). This type of resistance differs from non-specific pathotype resistance, which is characterized by greater resistance stability against a greater number of P. infestans pathotypes ( VAN DER PLANK, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The experiments 1, 2, and 3 were conducted from April 4 th to June 29 th (from early autumn to early winter), May 30 th to September 3rd (from late autumn to late winter), and August 3 rd to October 28 th (from mid-winter to mid-spring), respectively. In each experiment, there were two side-by-side trials, one for late blight (Trial 1) and the other for early blight (Trial 2); 'Ágata', an early-foliage-maturing cultivar that is susceptible to both late blight and early blight (DUARTE et al, 2012(DUARTE et al, , 2014, was used in all experiments. Each plot consisted of three rows measuring 4.0 m × 2.4 m, with 2.5 m alleyways between adjacent plots.…”
Section: Field Experiments Treatments and Inoculationsmentioning
confidence: 99%
“…When performing temporal analyses of plant diseases, the progress curve is the best representation of an epidemic. Interpreting the shape of these curves and determining certain parameters, such as the area under disease progress curve (AUDPC), are of critical importance to provide a better understanding of the behavior of epidemic and to develop effective disease management strategies (DUARTE et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As early as in the 19th century, the disease was shown to be caused by fungi of Alternaria spp., with A. solani and A. alternata being the most aggressive to Solanum tuberosum [ 1 ]. The fungi predominantly infect older tissues, and the disease symptoms start to appear at the lower leaves [ 2 ]. Hot and dry climate areas with alternating dry and rainy seasons are especially prone to early blight epiphytotics [ 3 ].…”
Section: Introductionmentioning
confidence: 99%